2020
DOI: 10.1111/jipb.12974
|View full text |Cite
|
Sign up to set email alerts
|

Induction of γ‐aminobutyric acid plays a positive role to Arabidopsis resistance against Pseudomonas syringae

Abstract: Gamma-aminobutyric acid (GABA) is an important metabolite which functions in plant growth, development, and stress responses. However, its role in plant defense and how it is regulated are largely unknown. Here, we report a detailed analysis of GABA induction during the resistance response to Pseudomonas syringae in Arabidopsis thaliana. While searching for the mechanism underlying the pathogen-responsive mitogenactivated protein kinase (MPK)3/MPK6 signaling cascade in plant immunity, we found that activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Recently, Deng et al [ 148 ] reported that activation of the mitogen-activated protein kinase (MPK3/MPK6) signaling cascade greatly induces GABA biosynthesis in Arabidopsis ( Table 3 ). The gad1/2/4 triple and gad1/2/4/5 quadruple mutants, in which the GABA levels are extremely low and the Glu and alanine levels are compromised, are more susceptible to both Pst and Pst-avrRpt2.…”
Section: Gaba Metabolism and Its Response To Biotic Stressmentioning
confidence: 99%
“…Recently, Deng et al [ 148 ] reported that activation of the mitogen-activated protein kinase (MPK3/MPK6) signaling cascade greatly induces GABA biosynthesis in Arabidopsis ( Table 3 ). The gad1/2/4 triple and gad1/2/4/5 quadruple mutants, in which the GABA levels are extremely low and the Glu and alanine levels are compromised, are more susceptible to both Pst and Pst-avrRpt2.…”
Section: Gaba Metabolism and Its Response To Biotic Stressmentioning
confidence: 99%
“…GABA metabolism can coordinate the carbon and nitrogen balance of mitochondrial dysfunction mutant and improve its photosynthetic efficiency under salt stress (Akcay et al 2012). Previous researches have shown that environmental stress promotes the production of GABA in plants and the accumulation of GABA improves tolerance to drought stress (Serraj et al 1998), salt stress (Al-Quraan et al 2013, insect injury (Bown et al 2006) and pathogen infection (Deng et al 2020). In Arabidopsis, GABA can reduce stomatal opening and transpirational water loss by negatively regulating the anion transporter located in the vacuole membrane of stomatal guard cells under drought conditions (Xu et al 2021).Under salt stress, the application of exogenous GABA significantly increased the content of endogenous GABA, enhanced the antioxidant activity and reduced the damage of cell membrane in maize seedlings (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among MAPK proteins, MPK3 and MPK6, together with their upstream MAPKKs, MKK4 and MKK5, are involved in a number of biological processes. They are implicated in plant innate immunity (Asai et al, 2002), stomatal patterning (Wang et al, 2007), floral organ abscission and lateral root formation (Cho et al, 2008;Zhu et al, 2019), ovule development (Wang et al, 2008), and plant defense (; Deng et al, 2020;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%